До вибору доповняльної умови для рівнянь Матісона-Папапетру - Пляцко, Р.; Стефанишин, О.; Феник, М. (Праці наукового товариства ім. Шевченка, 2011)
In the context of choosing the adequate supplementary condition for the Mathisson Papapetrou equations, in the case of a Schwarzschild metric, the possibility of using the Tulczyjew-Dixon condition for highly relativistic motions of a spinning particle relative to the source of the gravitational field is investigated. The estimate of the critical value of the tangential velocity of the particle when this condition cannot be used is obtained.